2009
DOI: 10.1121/1.3216912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of source-to-listener distance and masking on perception of cochlear implant processed speech in reverberant rooms

Abstract: Two experiments examined the effects of source-to-listener distance ͑SLD͒ on sentence recognition in simulations of cochlear implant usage in noisy, reverberant rooms. Experiment 1 tested sentence recognition for three locations in the reverberant field of a small classroom ͑volume= 79.2 m 3 ͒. Subjects listened to sentences mixed with speech-spectrum noise that were processed with simulated reverberation followed by either vocoding ͑6, 12, or 24 spectral channels͒ or no further processing. Results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 58 publications
0
11
1
1
Order By: Relevance
“…Only a few studies were reported, and those studies involved primarily vocoder simulations conducted with normal-hearing listeners. For instance, in the studies by Poissant et al (2006) and Whitmal and Poissant (2009), normal-hearing adult listeners were presented with reverberant stimuli processed into 6-24 channels using tone-excited vocoders. Percent correct recognition scores were found to be significantly worse when speech inside a reverberant field with RT 60 ¼ 0.7 s was vocoded using a small number of channels (Whitmal and Poissant, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies were reported, and those studies involved primarily vocoder simulations conducted with normal-hearing listeners. For instance, in the studies by Poissant et al (2006) and Whitmal and Poissant (2009), normal-hearing adult listeners were presented with reverberant stimuli processed into 6-24 channels using tone-excited vocoders. Percent correct recognition scores were found to be significantly worse when speech inside a reverberant field with RT 60 ¼ 0.7 s was vocoded using a small number of channels (Whitmal and Poissant, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the studies by Poissant et al (2006) and Whitmal and Poissant (2009), normal-hearing adult listeners were presented with reverberant stimuli processed into 6-24 channels using tone-excited vocoders. Percent correct recognition scores were found to be significantly worse when speech inside a reverberant field with RT 60 ¼ 0.7 s was vocoded using a small number of channels (Whitmal and Poissant, 2009). The authors concluded that in all conditions tested, the reverberation time and the directto-reverberant ratio (DRR) 1 had a negative impact on the speech identification performance of the listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Poissant et al (2006) and Whitmal and Poissant (2009) controlled the spectral resolution of normal-hearing listeners and showed a systematic degradation in speech identification as the number of vocoder channels decreased.…”
Section: Discussionmentioning
confidence: 98%
“…In general, if the space is surrounded by materials that are highly reflective (e.g., concrete, tile, wood flooring, bricks, and glass), RT 60 values are high. The effects of reverberation on speech identification for CI users has recently received extensive attention (e.g., Poissant et al 2006;Whitmal and Poissant 2009;Zheng et al 2011;Tillery et al 2012). In the present study, when the effect of reverberation was introduced, speech identification performance remained constant until RT 60 = 0.6, and then decreased significantly at RT 60 =1.0.…”
Section: Discussionmentioning
confidence: 99%
“…The study of cochlear implant users revealed the difficulties these users have in understanding speech within the school environment, suggesting that such students should position themselves nearer the speaker (teacher) to help speech understanding 29 .…”
Section: Resultsmentioning
confidence: 99%